Positive strain rate dependence: optimizing TRIP effect for high-speed deformation in lean duplex stainless steel - Yongxin Wang; Lei Chen; Xingzhou Cai; Motomichi Koyama; Zhenting Wang; Xiaolong Li; Zhikun Bai; Xiaocong Ma; Miao Jin (Materials Research Letters)
We developed a unique lean duplex stainless steel with a highly unstable austenite phase, exhibiting positive strain rate dependence in tensile properties. Specifically, increased strain rates enhanced the strength-ductility synergy. Adiabatic heating was actively utilized to stabilize austenite, extending the TRIP effect over a wide strain range and maintaining high strain hardening rates until a large strain particularly at high strain rates. Additionally, brittle cracking in ferrite and martensite was significantly reduced with increasing strain rate, resulting in a brittle-to-ductile transition. This discovery offers novel insights into alloy design strategies for metastable steels, improving production efficiency in forming processes.